2008
DOI: 10.1007/s12070-008-0085-y
|View full text |Cite
|
Sign up to set email alerts
|

Complete resolution of stage IIIB juvenile nasopharyngeal angiofibroma with radiation therapy

Abstract: Juvenile nasopharyngeal angiofi broma is a benign, locally aggressive, vascular tumour of adolescent males. Extension to intracranial cavity is not uncommon and presents diffi culties in management. Here we report a patient who had Radkowsky stage IIIB lesion, with blood supply from internal carotid artery. In view of anticipated problems with surgery, the patient was treated with 30 Gy in 15# external beam radiotherapy. On follow up, tumour was noted to disappear gradually overtime and at 3 years complete dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Conley et al also reported a case of orbital squamous cell carcinoma [10]. Only two studies have reported sarcomatous change in JNA postirradiation [11, 12], though possibility of the same have been put forth by many studies [4, 13]. As in our patient, radiotherapy has been used in the adjuvant setting as well.…”
Section: Discussionmentioning
confidence: 54%
“…Conley et al also reported a case of orbital squamous cell carcinoma [10]. Only two studies have reported sarcomatous change in JNA postirradiation [11, 12], though possibility of the same have been put forth by many studies [4, 13]. As in our patient, radiotherapy has been used in the adjuvant setting as well.…”
Section: Discussionmentioning
confidence: 54%